A randomized study comparing the pharmacokinetics of the potential biosimilar PF-06438179/GP1111 with Remicade® (infliximab) in healthy subjects (REFLECTIONS B537-01). (3rd April 2018) - Palaparthy, Ramesh; Udata, Chandrasekhar; Hua, Steven Y.; Yin, Donghua; Cai, Chun-Hua; Salts, Stephanie; Rehman, Muhammad I.; McClellan, Joseph; Meng, Xu
ABSTRACT: Background : To demonstrate pharmacokinetic (PK) similarity of PF-06438179/GP1111, a potential biosimilar to Remicade®, to Remicade® sourced from European Union (infliximab-EU) and United States (infliximab-US), and of infliximab-EU to infliximab-US. Methods : In this phase I, parallel-group, three-arm trial, healthy adult subjects were randomized to receive a single 10-mg/kg intravenous infusion of PF-06438179/GP1111, infliximab-EU, or infliximab-US. PK, and safety and immunogenicity evaluations were performed over 8 and 12 weeks, respectively. PK similarity was established if the 90% confidence intervals (CIs) of the test-to-reference ratios for PK parameters, Cmax, AUCT, and AUCinf, were within the 80.00–125.00% pre-specified equivalence window. Results : Of 151 subjects randomized, 146 received study treatment; 130 were eligible for PK similarity assessment. Serum concentration–time profiles were similar across the three treatments. The 90% CIs for test-to-reference ratios for Cmax, AUCT, and AUCinf were within 80.00–125.00% for comparison of PF-06438179/GP1111 to infliximab-EU and infliximab-US, and of infliximab-EU to infliximab-US. Similar numbers of subjects across treatment groups experienced adverse events. Anti-drug and neutralizing antibody profiles were largely similar among groups. Conclusions : This study demonstrated PK similarity of PF-06438179/GP1111 to infliximab-EU and infliximab-US, and of infliximab-EU to infliximab-US. All three products displayed comparable safety and immunogenicity profiles. Trial registration : CT.gov identifier NCT01844804